The effect of financial performance targets and financial stability on financial report fraud practices with independent commissioners as moderating variables (Empirical study on companies’ sector consumer goods industry period 2018 - 2022) - Suwardi, Arif Darmawan; Riyadi, Sugeng (Global Academy of Business Studies, 2024)
Purpose: This study examines the influence of setting financial performance targets and the condition of a company's financial stability on financial statement fraud practices, with the presence of an independent board of commissioners as a moderating variable. Research Methodology: A quantitative approach was applied using secondary data from 33 firms, yielding 165 observations. Panel data regression and Moderated Regression Analysis (MRA) with EViews software were used to test the hypotheses. Results: The findings show that financial performance targets and financial stability do not significantly affect financial statement fraud. The independent board of commissioners cannot moderate these relationships. However, independent commissioners have a significant negative effect, helping to reduce fraudulent practices. Conclusions: The study concludes that financial targets and stability are not decisive in fraud practices, while independent commissioners play a preventive role but not as moderating variables. Limitations: The scope is limited to consumer goods companies, profitability indicators, and the 2018–2022 period, without considering the broader external factors. Contribution: This study provides empirical evidence for corporate governance studies in Indonesia and highlights the importance of strengthening the role of independent commissioners to enhance oversight and reduce fraud risk.